Changing the thermostability of Bacillus licheniformis a-amylase - De Cordt, S. (1993)
We applied "solvent engineering" (i.e. variation of environmental conditions) to and/or irnrnobilized Baci//us licheniforrnis a-amylase covalently onto porous glass beads. In this way, important alterations in its thermostability characteristics (kinactrE Ainactw) ere achieved.